Sekuritisasi Ancaman Insurgensi dan Terorisme Asia Tenggara: Studi Kasus Kelompok Abu Sayyaf di Filipina - Indrawan, Jerry; Supriyadi, Didik (Prodi Ilmu Politik, 2025)
Abu Sayyaf is a terrorist group that has the potential to threaten stability and security in the Southeast Asia region. Abu Sayyaf's terrorist actions have entered the territory of neighboring countries of the Philippines. Handling it has become more comprehensive and needs to involve other countries, both bilaterally and regionally. Southeast Asian waters are declared as areas prone to crime so that cooperation and security issues in the military, political, and law enforcement fields between ASEAN members need to be improved. Terrorist actions carried out by the insurgent groups Abu Sayyaf and the Maute Clan have been involved with the terrorist organization IS (Islamic State). The convergence of insurgency and terrorism requires counterinsurgency and counterterrorism strategies. This paper will discuss the insurgency and terrorism of the Abu Sayyaf group from a securitization perspective. The theories used are the Copenhagen school and securitization. This study uses a descriptive qualitative approach through literature studies.